toner
The toner formulation addresses charge stability and image scratch resistance issues by using a polyester resin with specific monomer units in polymer A, enhancing charging stability and adhesion to paper.
Patent Information
- Application Number
- JP2021031660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-01
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-03-01
AI Technical Summary
Existing toners experience issues with charge stability and image scratch resistance, particularly when used in environments where air conditioning is off, leading to decreased charge amounts and low adhesion to paper, resulting in image scratches.
A toner formulation with a binder resin containing a polyester resin and a polymer A, where the polymer A has specific monomer units with controlled SP values and content ratios, enhancing charging stability and image scratch resistance by improving affinity and dispersibility of silicone moieties.
The toner achieves improved charging stability and enhanced image scratch resistance by optimizing the interaction between polyester and silicone components, ensuring stable charge retention and better adhesion to paper.
Smart Images

Figure 0007599992000001 
Figure 0007599992000002 
Figure 0007599992000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a toner used in electrophotography, electrostatic recording, electrostatic printing, toner jet methods, and the like. [Background technology]
[0002] In recent years, there has been a demand for toners that provide high color stability in printed images during image formation. Specifically, there has been a demand for toners that are less susceptible to change in charge amount in order to stabilize development efficiency even during long-term image output. For example, Patent Document 1 discloses an approach to improve the charging stability by using a composite polyester resin in which silicone oil is bonded to a polyester resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-12657 A Summary of the Invention [Problem to be solved by the invention]
[0004] When the copier is operated in an air-conditioned environment, such as after the summer vacation, the charge amount of the toner described in the above document also decreases, and it was found that further improvement is necessary. On the other hand, as full-color printers have started to be applied to the printing market, the scratch resistance of printed images is becoming important. When a printed image made of toner with low adhesion to paper is scratched with a fingernail, the toner may peel off from the paper. When the composite polyester described above is used as the main binder of the toner, the adhesion between the toner and the paper is low due to its low polarity. As a result, "image scratches" occur, and it was found that further improvement is necessary. The present disclosure provides a toner that has further improved charging stability and excellent image scratch resistance. [Means for solving the problem]
[0005] The present disclosure relates to a toner having toner particles containing a binder resin and a polymer A, The binder resin contains a polyester resin having a structure represented by the following formula (B): In the following formula (B), R X each independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, TIFF0007599992000001.tif17170, and -R 20 NH 2 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10 to 80. The polymer A has a first monomer unit having a structure represented by the following formula (I) and a second monomer unit different from the first monomer unit, In the following formula (I), R Z1 represents a hydrogen atom or a methyl group, R represents an alkyl group having 18 to 36 carbon atoms, The content ratio of the first monomer unit in the polymer A is 5.0 mol % to 60.0 mol % based on the total number of moles of the content of the second monomer unit in the polymer A is 20.0 mol % to 95.0 mol % based on the total number of moles of all monomer units in the polymer A, The SP value of the first monomer unit is SP1 (J / cm 3 ) 0.5 The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 In the structure represented by formula (B), -(Si(R X ) 2 O) n -Si(R X) 2 - The SP value of the silicone part represented by SP3 (J / cm 3 ) 0.5 The toner satisfies the following formulas (1) to (3). SP1≦18.4 (1) 21.0≦SP2 (2) SP1-SP3 <SP2-SP1 ···(3)
[0006] [ka] Effect of the Invention
[0007] The present disclosure can provide a toner that has further improved charging stability and excellent image scratch resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The expressions "XX or more and YY or less" or "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. The (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester. The term "monomer unit" refers to the reacted form of a monomer substance in a polymer, and one section of carbon-carbon bond in the main chain formed by polymerization of a vinyl monomer in a polymer is defined as one unit. The vinyl monomer can be represented by the following formula (Z). [ka] [In formula (Z), Z 1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group); Z 2 represents an optional substituent. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.
[0009] The present disclosure relates to a toner having toner particles containing a binder resin and a polymer A, The binder resin contains a polyester resin having a structure represented by the following formula (B): In the following formula (B), R X each independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, TIFF0007599992000004.tif17170, and -R 20 NH 2 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10 to 80. The polymer A has a first monomer unit having a structure represented by the following formula (I) and a second monomer unit different from the first monomer unit, In the following formula (I), R Z1 represents a hydrogen atom or a methyl group, R represents an alkyl group having 18 to 36 carbon atoms, the content of the first monomer unit in the polymer A is 5.0 mol % to 60.0 mol % based on the total number of moles of all monomer units in the polymer A, the content of the second monomer unit in the polymer A is 20.0 mol % to 95.0 mol % based on the total number of moles of all monomer units in the polymer A, The SP value of the first monomer unit is SP1 (J / cm 3 ) 0.5 The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 In the structure represented by formula (B), -(Si(R X ) 2 O) n -Si(R X ) 2 - The SP value of the silicone part represented by SP3 (J / cm 3 )0.5 The toner satisfies the following formulas (1) to (3). SP1≦18.4 (1) 21.0≦SP2 (2) SP1-SP3 <SP2-SP1 ···(3)
[0010] [ka]
[0011] In the structure represented by formula (B), -(Si(R X ) 2 O) n -Si(R X ) 2 The moiety represented by -, that is, the structure excluding A and B in formula (B), is also referred to as a silicone moiety. As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by controlling the molar ratio, SP value, and magnitude relationship of the SP value of the monomer unit represented by formula (I) of polymer A added to a polyester resin having a structure represented by formula (B) within specific ranges. The present inventors speculate as follows about the reason why the above problem has been solved.
[0012] The polyester resin having the structure represented by formula (B) is a resin in which a polyester moiety with high polarity is bonded (for example, covalently bonded) to a silicone moiety with low polarity. The silicone moiety has low polarity, which results in good charging stability, but since charge leakage occurs from the polyester moiety with high polarity, further improvement in charging stability was required when left for a long period of time. Furthermore, the silicone moiety has low adhesion to paper, which resulted in issues with image scratch resistance.
[0013] Therefore, the present inventors have investigated a toner in which a crystalline vinyl resin having a monomer unit with a high SP value is added to a polyester resin having a structure represented by formula (B), and have found that the charging stability is further improved and the image scratch resistance is also improved. When the first monomer unit of polymer A satisfies the above formula (1): SP1 ≦ 18.4, the affinity between the silicone moiety of the polyester resin having the structure represented by formula (B) and the first monomer unit of polymer A increases. When the second monomer unit of polymer A satisfies the above formula (2): 21.0 ≦ SP2, the affinity between the polyester moiety of the polyester resin having the structure represented by formula (B) and the second monomer unit of polymer A increases. Therefore, polymer A functions as a dispersant for the silicone moiety, and the dispersibility of the silicone moiety in the toner is improved. As a result, the silicone moiety can suppress the charge leakage from the polyester moiety, and the charging stability can be improved. Also, since polymer A is a crystalline resin, compared with the polyester resin having the structure represented by formula (B), the viscosity during fixing becomes lower and it precipitates on the surface of the toner particles. Since there is a silicone moiety with a small surface free energy, polymer A can dissolve and spread on the paper. When the above formula (3): SP1 - SP3 < SP2 - SP1 is satisfied, the hydrophobicity inside the toner increases with respect to the second monomer unit of polymer A, and the second monomer unit of polymer A is likely to be oriented toward the paper side, so that a pseudo-crosslinked structure with the paper can be formed. As a result, the adhesion between the image and the paper is improved, and the image scratch resistance is improved.
[0014] Polymer A has a first monomer unit having a structure represented by the following formula (I) and a second monomer unit different from the first monomer unit. And polymer A has a crystalline site derived from a long-chain alkyl group present in the first monomer unit. The first monomer unit is derived from at least one first polymerizable monomer selected from the group consisting of (meth)acrylic acid esters having an alkyl group with 18 to 36 carbon atoms. By setting the number of carbon atoms within the above range, the affinity between polymer A and the silicone moiety of the polyester resin having the structure represented by formula (B) increases, and the charging stability and the image scratch resistance become good. The first (or second) monomer unit is, for example, a monomer unit obtained by addition polymerization (vinyl polymerization) of a first (or second) polymerizable monomer.
[0015] [ka]
[0016] [In formula (I), R Z1 represents a hydrogen atom or a methyl group, and R represents an alkyl group having 18 to 36 carbon atoms (preferably a linear alkyl group having 18 to 30 carbon atoms).]
[0017] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.]. Among these, from the viewpoint of low temperature fixability, preferably at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with a carbon number of 18 to 36, more preferably at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with a carbon number of 18 to 30. Even more preferred is at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate, and even more preferred is at least one selected from the group consisting of linear behenyl (meth)acrylate. The first polymerizable monomer may be used alone or in combination of two or more kinds.
[0018] The content of the first monomer unit in polymer A is 5.0 mol % to 60.0 mol % based on the total number of moles of all monomer units in polymer A, and preferably 20.0 mol % to 40.0 mol %. By ensuring that the content is within the above range, the silicone moiety can be dispersed in the toner, improving the charging stability, and the dissolving and spreading of polymer A during fixing is promoted, improving image scratch resistance. The content of the first monomer unit in polymer A is preferably 40.0% by mass to 85.0% by mass, more preferably 50.0% by mass to 80.0% by mass, and further preferably 60.0% by mass to 75.0% by mass.
[0019] The SP value of the first monomer unit in polymer A is SP1 (J / cm 3 ) 0.5 When set to , the following formula (1) is satisfied. It is further preferable that the following formula (1)' is satisfied. SP1≦18.4 (1) 18.2≦SP1≦18.4 (1)' Here, the SP value is an abbreviation for solubility parameter, and is a value that serves as an index of solubility. The calculation method will be described later. The unit of SP value is (J / cm 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / cm 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of When the SP value of the first monomer unit is within the above range, the affinity between the first monomer unit and the silicone portion of the polyester resin having the structure represented by formula (B) is increased, resulting in good charging stability and image scratch resistance.
[0020] In addition, polymer A has a second monomer unit different from the first monomer unit. The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 When set to , the following formula (2) is satisfied. It is further preferable that the following formula (2)' is satisfied. 21.0≦SP2 (2) 25.0≦SP2≦30.0 (2)' When the SP value of the second monomer unit is within the above range, the affinity between the second monomer unit and the polyester moiety is increased, the charging stability is improved, and a crosslinked structure can be formed between the paper and the toner, resulting in good image scratch resistance.
[0021] In addition, the silicone moiety (-(Si(R X ) 2 O) n -Si(R X ) 2 -) SP value of SP3 (J / cm 3 ) 0.5 Then, the following formula (3) is satisfied. SP1-SP3 <SP2-SP1 ···(3) The fact that SP1, SP2, and SP3 satisfy the above formula means that the affinity between the first monomer unit and the silicone moiety is higher than the affinity between the first monomer unit and the second monomer unit. By satisfying the above, the dispersibility of the silicone moiety in the toner is improved, the charging stability is improved, and the melting and spreading of polymer A during fixing is promoted, resulting in good image scratch resistance.
[0022] The content of the second monomer unit in polymer A is 20.0 mol % to 95.0 mol % based on the total number of moles of all monomer units in polymer A, preferably 30.0 mol % to 70.0 mol %, and more preferably 40.0 mol % to 60.0 mol %. When the content ratio is within the above range, the affinity between the second monomer unit and the polyester moiety is increased, improving the charging stability, and the paper and the second monomer unit can form a crosslinked structure, improving the image scratch resistance. The content of the second monomer unit in polymer A is preferably from 10.0% by mass to 50.0% by mass, more preferably from 15.0% by mass to 40.0% by mass, and further preferably from 15.0% by mass to 30.0% by mass.
[0023] The second monomer unit is preferably at least one selected from the group consisting of a monomer unit represented by the following formula (II) and a monomer unit represented by the following formula (III).
[0024] [ka]
[0025] (In formula (II), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 1 is a nitrile group (-C≡N), Amide group (-C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy groups, -COOR 11 (R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), Urethane group (-NHCOOR 12 (R 12 represents an alkyl group having 1 to 4 carbon atoms; Urea group (-NH-C(=O)-N(R 13 ) 2 (Two R 13 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH 2 )2 NHCOOR 14 (R 14 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH 2 ) 2 -NH-C(=O)-N(R 15 ) 2 (Two R 15 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 2 represents a hydrogen atom or a methyl group. (In formula (III), R 3 represents an alkyl group having 1 to 4 carbon atoms, R 4 represents a hydrogen atom or a methyl group.
[0026] When the second monomer unit contains at least one selected from the group consisting of formulas (II) and (III), the affinity with the polyester moiety is increased, the charging stability is improved, and a crosslinked structure with paper can be formed, resulting in good image scratch resistance. The second monomer unit may be used alone or in combination of two or more kinds. When two or more kinds of the first monomer units are used in combination in the polymer A, the content of the monomer units is the sum of the contents of the respective monomer units. The same applies to the second monomer unit.
[0027] As the second polymerizable monomer forming the second monomer unit, for example, among the following, a polymerizable monomer satisfying the formulas (2) and (3) can be used. The second polymerizable monomer may be used alone or in combination of two or more kinds. Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like. Monomers having an amide group: for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method, etc.
[0028] Monomers having a urethane group; for example, alcohols having 2 to 22 carbon atoms having an ethylenically unsaturated bond (e.g., 2-hydroxyethyl methacrylate, vinyl alcohol, etc.) and isocyanates having 1 to 30 carbon atoms [monoisocyanate compounds (benzenesulfonyl isocyanate, tosyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, t-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, diisocyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, and 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, etc.) , dodecamethylene diisocyanate and 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate and hydrogenated tetramethylxylylene diisocyanate, etc.), and aromatic A monomer obtained by reacting an aromatic diisocyanate compound (such as phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate) by a known method, and Alcohols with 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropyl alcohol, butanol, t-butyl alcohol, pentanol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecyl alcohol, lauryl alcohol, dodecyl alcohol, myristyl alcohol, pentadecyl alcohol, cetanol, heptadecanol, stearyl alcohol, isostearyl alcohol, elaidyl alcohol, oleyl alcohol, linoleyl alcohol, linoleyl alcohol, and monomers obtained by reacting, by a known method, an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond [2-isocyanatoethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, etc.], and the like.
[0029] Monomers having a urea group: for example, monomers obtained by reacting an amine having 3 to 22 carbon atoms [primary amines (such as normal butylamine, t-butylamine, propylamine, and isopropylamine), secondary amines (such as di-normal ethylamine, di-normal propylamine, and di-normal butylamine), aniline, and cycloxylamine] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, and the like. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate, etc.
[0030] Among them, it is preferable to use a monomer having a nitrile group, an amide group, a urethane group, a hydroxy group, or a urea group, and more preferably a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a urethane group, a hydroxy group, and a urea group, and an ethylenically unsaturated bond.
[0031] As the second polymerizable monomer, vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate are also preferably used.
[0032] The second polymerizable monomer preferably has an ethylenically unsaturated bond, and more preferably has one ethylenically unsaturated bond. Moreover, the second polymerizable monomer is more preferably at least one selected from the group consisting of the following formulae (C) and (D).
[0033] [ka]
[0034] (In formula (C), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 1 is a nitrile group (-C≡N), Amide group (-C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy groups, -COOR 11 (R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), Urethane group (-NHCOOR 12 (R 12 represents an alkyl group having 1 to 4 carbon atoms; Urea group (-NH-C(=O)-N(R 13 ) 2 (Two R 13 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH 2 ) 2 NHCOOR 14 (R14 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH 2 ) 2 -NH-C(=O)-N(R 15 ) 2 (Two R 15 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 2 represents a hydrogen atom or a methyl group. (In formula (D), R 3 represents an alkyl group having 1 to 4 carbon atoms, R 4 represents a hydrogen atom or a methyl group.
[0035] When multiple types of monomer units satisfying the above-mentioned requirements for the first monomer unit are present in the polymer A, the value of SP1 in the formula (3) is a weighted average of the SP values of the respective monomer units. 11 The monomer unit A is A mol % based on the total number of moles of the monomer units satisfying the requirement of the first monomer unit, and the SP value is SP 12 The SP value (SP1) when the monomer unit B is contained in an amount of (100-A) mol % based on the total number of moles of the monomer units satisfying the requirement of the first monomer unit is: SP1=(SP 11 ×A+SP 12 ×(100-A)) / 100 The calculation is similar to the above when three or more monomer units satisfying the requirements for the first monomer unit are included. Even when a plurality of second monomer units and / or silicone moieties are present, in the calculation of formula (3), SP2 and / or SP3 are determined in the same manner as SP1.
[0036] The polymer A is preferably a vinyl polymer. Examples of the vinyl polymer include polymers of monomers containing ethylenically unsaturated bonds. The ethylenically unsaturated bond refers to a carbon-carbon double bond capable of radical polymerization, and examples of the ethylenically unsaturated bond include vinyl, propenyl, acryloyl, and methacryloyl groups. The acid value Av of the polymer A is preferably 30.0 mgKOH / g or less, more preferably 20.0 mgKOH / g or less. The lower limit is not particularly limited, but is preferably 0 mgKOH / g or more. When the acid value is 30.0 mgKOH / g or less, the crystallization of the polymer A is not easily inhibited, and the melting point is well maintained.
[0037] Furthermore, the weight average molecular weight (Mw) of the tetrahydrofuran (THF) soluble matter of the polymer A measured by gel permeation chromatography (GPC) is preferably from 10,000 to 200,000, more preferably from 20,000 to 150,000. When Mw is within the above range, elasticity at around room temperature is easily maintained. The melting point of the polymer A is preferably from 50° C. to 80° C., and more preferably from 53° C. to 70° C. When the melting point is 50° C. or higher, the charging stability is improved, and when the melting point is 80° C. or lower, the image scratch resistance is improved.
[0038] The polymer A may contain a third monomer unit having a third polymerizable monomer not included in the range of either the above formula (1) or (2) (i.e., different from the first polymerizable monomer and the second polymerizable monomer) as a constituent component, within a range that does not impair the molar ratio of the first monomer unit derived from the above-mentioned first polymerizable monomer and the second monomer unit derived from the second polymerizable monomer. The third monomer unit has a structure obtained by addition polymerization of the third polymerizable monomer. As the third polymerizable monomer, among the monomers listed in the section of the second polymerizable monomer, a monomer not satisfying formula (2) can be used. In addition, the following monomers which do not have the above-mentioned nitrile group, amide group, urethane group, hydroxy group, urea group, or carboxy group can also be used. For example, styrene and its derivatives such as styrene and o-methylstyrene, and (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. The third polymerizable monomer is preferably at least one selected from the group consisting of styrene, methyl methacrylate, and methyl acrylate. When these satisfy the formula (2), they can be used as the second polymerizable monomer.
[0039] The content of polymer A is preferably 1.0 parts by mass or more and 10.0 parts by mass or less, and more preferably 3.0 parts by mass or more and 8.0 parts by mass or less, relative to 100 parts by mass of binder resin. When the content of polymer A is within the above range, the interaction between polymer A and the polyester resin having the structure represented by formula (B) is promoted, and the charging stability and image scratch resistance are improved.
[0040] It is particularly preferred that the first monomer unit is a monomer unit derived from behenyl acrylate. That is, in formula (I), R Z1 It is particularly preferred that R is a hydrogen atom and R is an alkyl group having 22 carbon atoms. By using behenyl acrylate, a polyester having a structure represented by formula (B) can be obtained. By dispersing the silicone portion of the resin in the toner, the charging stability is improved, and the polymer A can be effectively melted and spread during fixing, resulting in better image scratch resistance.
[0041] The polyester resin having the structure represented by formula (B) is -(Si(R X ) 2 O) n -Si(R X ) 2That is, the polyester resin having the structure represented by formula (B) has a silicone moiety represented by the following formula (B'). The content of silicone moieties in the polyester resin having the structure represented by formula (B) is preferably from 0.5% by mass to 5.0% by mass, and more preferably from 2.0% by mass to 4.0% by mass. By having the content of the silicone moiety within the above range, the dispersibility of the silicone moiety in the toner is improved due to the interaction with polymer A, and the surface free energy during fixing is effectively reduced, thereby promoting the dissolution and spreading of polymer A.
[0042] [ka]
[0043] In formula (B´), R X and n are the same as in formula (B). X each independently represents a hydrogen atom, a methyl group, or a phenyl group. n is the average number of repetitions of the siloxane unit and represents an integer of 10 to 80 (preferably 20 to 65). In formulas (B) and (B'), R X However, it is preferable that both of them are methyl groups. This increases the affinity with the first monomer unit of the polymer A, and improves the charging stability and image scratch resistance.
[0044] The binder resin used in the toner will be described. The binder resin contains a polyester resin having a structure represented by formula (B): In addition to the polyester resin having a structure represented by formula (B), the binder resin may contain other resins. Other resins include polyester resin, polyurethane resin, epoxy resin, phenol resin, and hybrid resins in which two or more of these resins are bonded together. In the binder resin, the content of the polyester resin having the structure represented by formula (B) is preferably 50% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more. The upper limit is not particularly limited, but is preferably 100% by mass or less. These values can be arbitrarily combined. By using the polyester resin having the structure represented by formula (B) as the main component of the binder resin, it is possible to effectively obtain the above-mentioned interaction with the polymer A.
[0045] The polyester resin having a structure represented by formula (B) has a silicone moiety and a polyester moiety represented by formula (B'). The polyester moiety of the polyester resin having a structure represented by formula (B) is preferably an amorphous polyester resin. The components constituting the polyester moiety of the polyester resin having the structure represented by formula (B) will be described in detail. The following components can be used singly or in combination depending on the type and application. Examples of the divalent carboxylic acid component constituting the polyester moiety include the following dicarboxylic acids or derivatives thereof. Benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides or lower alkyl esters; alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides or lower alkyl esters; alkenylsuccinic acids or alkylsuccinic acids having an average carbon number of 1 to 50, or their anhydrides or lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides or lower alkyl esters.
[0046] On the other hand, examples of the dihydric alcohol component constituting the polyester moiety include the following. Ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 1,4-cyclohexanedimethanol (CHDM), hydrogenated bisphenol A, bisphenol and its derivatives represented by formula (I-1): and diols represented by formula (I-2).
[0047] [ka]
[0048] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.)
[0049] [ka]
[0050] (In the formula, R' is an ethylene or propylene group, x' and y' are each an integer of 0 or more, and the average value of x'+y' is 0 or more and 10 or less.)
[0051] The components constituting the polyester segment may contain, in addition to the above-mentioned divalent carboxylic acid component and divalent alcohol component, a trivalent or higher carboxylic acid component and a trivalent or higher alcohol component. The trivalent or higher carboxylic acid component is not particularly limited, but examples thereof include trimellitic acid, trimellitic anhydride, pyromellitic acid, etc. Furthermore, the trivalent or higher alcohol component includes trimethylolpropane, pentaerythritol, glycerin, etc. The polyester moiety may contain, in addition to the above-mentioned compounds, a monovalent carboxylic acid component and a monovalent alcohol component as constituents.Specific examples of the monovalent carboxylic acid component include palmitic acid, stearic acid, arachidic acid, behenic acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, lactoseric acid, tetracontanoic acid, and pentacontanoic acid. Examples of the monohydric alcohol component include behenyl alcohol, ceryl alcohol, melissyl alcohol, and tetracontanol. The content of the polyester moiety in the polyester resin having the structure represented by formula (B) is preferably from 95.0% by mass to 99.5% by mass, and more preferably from 96.0% by mass to 98.0% by mass.
[0052] The components constituting the silicone moiety of the polyester resin having the structure represented by formula (B) are described in detail below. The following components can be used singly or in combination depending on the type and application. The silicone moiety is a structure represented by the formula (B') (-(Si(R X ) 2 O) n -Si(R X ) 2 -). As a component for forming a silicone moiety in the polyester resin having the structure represented by formula (B), a silicone oil having a functional group at the end of formula (B') that chemically reacts with polyester can be used. Examples of the functional group that reacts with polyester include a hydroxyl group, a carboxyl group, an epoxy group, and an amino group.
[0053] The functional group at the end of the silicone oil is preferably a hydroxy group or a carboxy group in order to control the reactivity with polyester. The valence of the functional group of the silicone oil is preferably 1, 2, or 3 or more. By introducing a silicone moiety into the main skeleton of the polyester, the interaction with the polymer A can be controlled, and the charging stability and image scratch resistance can be improved. Therefore, it is preferable to use a divalent silicone oil having functional groups at both ends of the silicone oil. More preferably, it is a silicone oil having a substituent containing a hydroxyl group at both ends of the formula (B'). The substituent containing a hydroxyl group is, for example, -(CH 2 ) p -O-(CH 2 ) q -OH In the formula, p is an integer of 1 to 3, and q is an integer of 1 to 3.
[0054] The method for producing the polyester resin having the structure represented by formula (B) is not particularly limited, and can use a known method. For example, the above-mentioned divalent carboxylic acid component, divalent alcohol component, and silicone oil having a functional group are polymerized through esterification reaction or ester exchange reaction and condensation reaction to produce the polyester resin having the structure represented by formula (B). The polymerization temperature is not particularly limited, but is preferably in the range of 180° C. to 290° C. In polymerizing the polyester resin, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. The softening point of the polyester resin having the structure represented by formula (B) is preferably from 85° C. to 150° C., and more preferably from 100° C. to 150° C. When the softening point of the polyester resin having the structure represented by formula (B) is within the above range, the charging stability is improved and the image scratch resistance is also improved.
[0055] The toner may contain wax. Examples of the wax include the following. Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Among these waxes, from the viewpoint of improving low-temperature fixing property and hot offset resistance, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax.
[0056] The wax content is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the binder resin. In addition, in the endothermic curve during heating measured by a differential scanning calorimeter (DSC), the peak temperature (melting point) of the maximum endothermic peak of the wax in the temperature range of 30°C to 200°C is ) is preferably 50° C. or higher and 140° C. or lower, and more preferably 60° C. or higher and 105° C. or lower.
[0057] The toner may contain a colorant. Examples of the colorant include the following. Examples of black colorants include carbon black, and a mixture of a yellow colorant, a magenta colorant, and a cyan colorant toned to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image. Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0058] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Cyan toner dyes include CI Solvent Blue 70. Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162. The content of the colorant is preferably 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0059] The toner may contain a charge control agent, if necessary. Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes. The charge control agent may be added internally or externally to the toner particles. The amount of the charge control agent added is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0060] The toner may contain inorganic fine particles as required. The additive may be added internally to the toner particles or may be mixed with the toner particles as an external additive. As the external additive, inorganic fine particles such as silica, titanium oxide, strontium titanate, and aluminum oxide are preferable. More preferably, low resistance particles such as silica and strontium titanate are preferable from the viewpoint of development stability. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof. As an external additive to improve fluidity, 2 / g or more 400m 2 / g or less, and for durability stabilization, a specific surface area of 10 m 2 / g or more 50m 2 In order to simultaneously improve the flowability and stabilize the durability, inorganic fine particles having a specific surface area within the above range may be used in combination. The content of the external additive is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.
[0061] The toner can be used as a one-component developer, but it is more preferable to mix the toner with a magnetic carrier and use it as a two-component developer, in that stable images can be obtained over a long period of time. Examples of magnetic carriers that can be used include generally known magnetic carriers such as surface-oxidized iron powder, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles, oxide particles, and magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state. When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio, in terms of the toner concentration in the two-component developer, is preferably 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less.
[0062] [Manufacturing method] The method for producing the toner particles is not particularly limited, and any of the conventionally known production methods such as an emulsion aggregation method, a melt kneading method, and a dissolution suspension method can be used. The obtained toner particles may be used as a toner as it is, or an external additive may be mixed (external addition) with the obtained toner particles to obtain a toner. Examples of the external additive include inorganic fine particles such as silica, alumina, titania, and calcium carbonate, and resin particles such as vinyl resin, polyester resin, and silicone resin. These inorganic fine powders and resin particles function as external additives for charge control, flow aid, cleaning aid, and the like. Examples of the mixing device include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).
[0063] Specific examples of the toner production method using the melt-kneading method will be described below, but the present invention is not limited to these. <Melt kneading method> First, in the raw material mixing step, predetermined amounts of the binder resin and polymer A, as well as wax, colorant and other additives as required, are weighed out and mixed as toner raw materials. Examples of equipment used for mixing include Henschel mixer (manufactured by Nippon Coke Company); Super mixer (manufactured by Kawata Corporation); Rebocone (manufactured by Okawara Manufacturing Co., Ltd.); Nauta mixer, Turbulizer, Cyclomix (manufactured by Hosokawa Micron Corporation); Spiral Pin Mixer (manufactured by Pacific Machinery Works); and Loedige mixer (manufactured by Matsubo Corporation).
[0064] Next, the obtained mixture is melted and kneaded to melt the binder resin, and polymer A and the like are added thereto. (melt-kneading process). Examples of devices used for melt kneading include a TEM type extruder (manufactured by Toshiba Machine Co., Ltd.), a TEX twin screw kneader (manufactured by Japan Steel Works, Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), and Kneadex (manufactured by Mitsui Mining Co., Ltd.) Continuous kneaders such as single screw or twin screw extruders are preferred over batch kneaders because of their advantages such as the ability to perform continuous production. Next, the resulting molten and kneaded product is rolled using a two-roll mill or the like, and cooled by water cooling or the like.
[0065] The cooled material is then crushed to a desired particle size by using a crusher, hammer mill, feather mill, or the like to coarsely crush the material, and then by using a Cryptron System (Kawasaki Heavy Industries, Ltd.) or a Super Rotor (Nisshin Engineering, Inc.) to finely crush the material to obtain resin particles. The resin particles thus obtained may be classified into particles of a desired particle size to obtain toner particles. Apparatuses used for classification include Turboplex, Faculty, TSP, TTSP (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), etc.
[0066] Next, the measurement methods for each physical property will be described. <Method for measuring the content of each monomer unit in polymer A> The content ratio of monomer units derived from various polymerizable monomers in polymer A was measured by: 1 H-NMR was performed under the following conditions. Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 Measurement temperature: 30℃ Sample: 50 mg of the sample to be measured was placed in a sample tube with an inner diameter of 5 mm, and deuterated chloroform (CDCl 3 ) and dissolve in a thermostatic bath at 40°C. Obtained 1 From the H-NMR chart, a peak that is independent of the peaks that are attributable to the components of the first monomer unit and the components of other monomer units is selected, and the integral value S of this peak is 1 Similarly, a peak independent of the peaks attributable to the components of the second monomer unit is selected from the peaks attributable to the components of the other monomer units, and the integral value S of this peak is calculated. 2 Calculate. Furthermore, in the case where a third monomer unit is present, a peak independent of the peaks attributable to the constituent elements of the third monomer unit is selected from the peaks attributable to the constituent elements of the other monomer units, and the integral value S of this peak is calculated. 3 Calculate. The content ratio of the first monomer unit is the integral value S 1 , S 2 , and S 3 Using the above, it is calculated as follows. Note that n 1 , n 2 , n 3 is the number of hydrogens in the component to which the peak of interest for each site is assigned. Content of first monomer unit (mol%)= {(S 1 / n 1 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100 Similarly, the contents of the second monomer unit and the third monomer unit are determined as follows. Content of second monomer unit (mol%)= {(S 2 / n 2 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100 Content of third monomer unit (mol%)= {(S 3 / n 3 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100 In addition, in the case where a polymerizable monomer that does not contain a hydrogen atom in any component other than the vinyl group is used in the polymer A, 13The nucleus to be measured using 13C-NMR is 13 13C, and the measurement is performed in single pulse mode. 1 It is calculated in the same manner using 1H-NMR. In addition, when the toner is manufactured by the suspension polymerization method, the peaks of the release agent and other resins may overlap, and independent peaks may not be observed. As a result, there may be cases where the content ratio of the monomer units derived from the various polymerizable monomers in polymer A cannot be calculated. In such cases, polymer A' can be manufactured by performing the same suspension polymerization without using a release agent or other resins, and polymer A' can be regarded as polymer A and analyzed.
[0067] <Calculation method of SP value> SP values such as SP1 and SP2 are obtained as follows according to the calculation method proposed by Fedors. For each polymerizable monomer, for the atoms or atomic groups in the molecular structure, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol) are obtained from the table described in "Polym. Eng. Sci., 14(2), 147-154(1974)", and (4.184×ΣΔei / ΣΔvi) 0.5 is taken as the SP value (J / cm 3 ) 0.5 and used. Note that SP1 and SP2 are calculated by the above calculation method for the atoms or atomic groups of the molecular structure in the state where the double bond of the polymerizable monomer is cleaved by polymerization.
[0068] <Measurement of glass transition temperature (Tg) of the binder resin and melting peak temperature (melting point) of polymer A> The Tg and melting point of resins such as the binder resin and polymer A are measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments). The temperature correction of the device detection part uses the melting points of indium and zinc, and the heat correction uses the heat of fusion of indium. Specifically, about 3 mg of resin is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference, and measurement is performed under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 30℃ End of measurement temperature: 180℃ Measurements are performed in the measurement range of 30 to 180°C at a heating rate of 10°C / min. The temperature is raised to 180°C once and held for 10 minutes, then cooled to 30°C, and then raised again. During this second heating process, the specific heat change is obtained in the temperature range of 30 to 100°C. The point at which the line midway between the baselines before and after the specific heat change appears and the differential thermal curve intersect is the glass transition temperature (Tg) of the resin. Furthermore, the temperature at which the maximum endothermic peak occurs on the temperature-endothermic curve in the temperature range of 40° C. to 90° C. is defined as the melting peak temperature (Tp).
[0069] <Method for measuring softening point Tm> The softening point is measured using a constant load extrusion type capillary rheometer "Flow property evaluation device Flow Tester CFT-500D" (Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature can be obtained. The "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow characteristic evaluation device Flow Tester CFT-500D" is taken as the softening point. The melting temperature in the 1 / 2 method is calculated as follows. First, half the difference between the amount of piston descent Smax at the time when the outflow ends and the amount of piston descent Smin at the time when the outflow starts is calculated (this is called X; X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent on the flow curve is the sum of X and Smin is the melting temperature Tm (°C) in the 1 / 2 method. For the measurement sample, about 1.3 g of the sample is compression molded at about 10 MPa for about 60 seconds using a tablet molding compressor (for example, NT-100H, manufactured by NPE System Co., Ltd.) under an environment of 25°C to form a cylindrical shape with a diameter of about 8 mm, and this is used. The measurement conditions of CFT-500D are as follows. Test mode: Heating-up method Initial temperature: 50°C Final temperature: 200°C Measurement interval: 1.0°C Heating rate: 4.0°C / min Piston cross-sectional area: 1.000 cm 2 Test load (piston load): 10.0 kgf / cm 2 (0.9807 MPa) Preheating time: 300 seconds Diameter of die hole: 1.0 mm Length of die: 1.0 mm
[0070] <Measurement of molecular weight of Polymer A by GPC> The weight average molecular weight (Mw) of the THF-soluble component of Polymer A is measured by gel permeation chromatography (GPC) as follows. First, dissolve the sample in tetrahydrofuran (THF) over 24 hours at room temperature. Then, filter the obtained solution through a solvent-resistant membrane filter "Micron Disc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. Note that the concentration of the components soluble in THF in the sample solution is adjusted to be about 0.8 mass%. Using this sample solution, measurements are carried out under the following conditions. Apparatus: HLC8120 GPC (Detector: RI) (manufactured by Tosoh Corporation) Columns: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) Eluent: Tetrahydrofuran (THF) Flow rate: 1.0 ml / min Oven temperature: 40.0°C Sample injection volume: 0.10 ml In calculating the molecular weight of the sample, standard polystyrene resins (e.g., TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-8 A molecular weight calibration curve prepared using the following antibodies was used: F-0, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500 (manufactured by Tosoh Corporation).
[0071] <Measurement of Acid Value of Polymer A> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of polymer A is measured in accordance with JIS K 0070-1992, and specifically, is measured according to the following procedure. (1) Preparation of reagents Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 mL of water, and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is determined by placing 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, from the amount of potassium hydroxide solution required for neutralization. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998. (2) Operation (A) Main Test 2.0 g of the ground polymer A sample was precisely weighed into a 200 mL Erlenmeyer flask and dissolved in toluene / ethanol. Add 100 mL of a mixture of ethanol (2:1) and dissolve for 5 hours. Then, add a few drops of the phenolphthalein solution as an indicator and titrate with the potassium hydroxide solution. The end point of the titration is when the indicator remains a light red color for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used). (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (mL), C is the amount of potassium hydroxide solution added for the main test (mL), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).
[0072] <Measurement of weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0073] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 ml of the above-mentioned aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) In a state where the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic waves are applied for another 60 seconds. Continue ultrasonic dispersion. During ultrasonic dispersion, adjust the water temperature in the tank appropriately to be between 10℃ and 40℃. (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner particles are dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).
[0074] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (polyester resin having a structure represented by formula (B)) is separated from the insoluble matter (polymer A, wax, colorant, inorganic fine particles, etc.). Second separation: The insoluble matter obtained in the first separation (polymer A, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (polymer A, wax) is separated from the insoluble matter (colorant, inorganic fine particles, etc.). Third separation: The soluble fraction (polymer A, wax) obtained in the second separation is dissolved in chloroform at 23° C., and the soluble fraction (polymer A) and the insoluble fraction (wax) are separated. Based on the above separation, it is possible to analyze each material and calculate the content of each material.
[0075] <Confirmation of the Structure of Polyester Resin Having a Structure Represented by Formula (B)> The structure of the polyester resin having the structure represented by formula (B) is confirmed by the following method. R in formula (B) X The hydrocarbon group and silicone moiety are 13 C-NMR and solid state 29 Confirm by Si-NMR. ( 13 C-NMR measurement conditions) Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample: Deuterated chloroform soluble fraction of sample for NMR measurement Measurement temperature: room temperature Pulse mode: CP / MAS Measurement nuclear frequency: 123.25MHz ( 13 C) Reference substance: Adamantane (external standard: 29.5ppm) Sample rotation speed: 20kHz Contact time: 2ms Delay time: 2s Number of times accumulated: 1024 In this method, the methyl group bonded to the silicon atom (Si-CH 3 ) or phenyl group (Si-C 6 H 5 ) and other signals, R in formula (B) X Identify the hydrocarbon groups.
[0076] solid 29 Specifically, the Si-NMR measurement conditions are as follows: Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DD / MAS method 29 Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan:2000
[0077] <Measurement of the content of silicone moieties in polyester resin having a structure represented by formula (B)> The silicone moiety and polymer A content in the polyester resin having the structure represented by formula (B) were measured using the above-mentioned apparatus. 1 Confirm by H-NMR. ( 1 H-NMR measurement conditions) Sample: deuterated chloroform solubles Pulse condition: 5.0μs Frequency range: 10500Hz Number of times accumulated: 64 EXAMPLES
[0078] The present invention will be specifically described below based on examples. However, the present invention is not limited thereto. In the following formulations, parts are by weight unless otherwise specified.
[0079] <Production example of binder resin P1> Bisphenol A ethylene oxide (2.2 mole adduct): 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct): 50.0 mole parts Terephthalic acid: 90.0 parts by mole Trimellitic anhydride: 10.0 mol parts 97 parts of the above monomer for forming the polyester segment and 3 parts of silicone oil having hydroxy groups at both ends (KF-6001, Shin-Etsu Chemical Co., Ltd.) were mixed together with 500 ppm of titanium tetrabutoxide in a 5-liter autoclave. There is a reflux condenser, a water separator, and N 2 Equip the autoclave with a gas inlet tube, a thermometer, and a stirrer, and fill it with N 2 While introducing gas, a condensation polymerization reaction was carried out at 230° C. The reaction time was adjusted so as to obtain a desired softening point, and after the reaction was completed, the mixture was taken out of the vessel, cooled, and pulverized to obtain a binder resin P1. The content of the silicone moiety in the binder resin P1 was 3.0% by mass. The physical properties are shown in Table 1.
[0080] <Production Examples of Binder Resins P2 to P8> Binder resins P2 to P8 were obtained in the same manner as in the production example for binder resin P1, except that the amount of silicone oil added was changed so that the content of the silicone moiety was the value shown in Table 1, and Tm and Tg were changed by adjusting the reaction time.
[0081] [Table 1] According to KF-6001, in formula (B), R X are all methyl groups, and n is 38 A structure is obtained where: BPA-PO Propylene oxide adduct of bisphenol A (average number of moles added: 2.2 mol) BPA-EO Ethylene oxide adduct of bisphenol A (average number of moles added: 2.2 mol) TPA Terephthalic Acid TMA Trimellitic Anhydride
[0082] <Production Example of Polymer A1> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, methacrylonitrile, and styrene in the ratio shown below.) (Behenyl acrylate (first monomer) 67.0 parts (28.9 mol %)) (Methacrylonitrile (second monomer) 22.0 parts (53.8 mol%)) (Styrene (third monomer) 11.0 parts (17.3 mol %)) Polymerization initiator t-butyl peroxypivalate (NOF Corp.: Perbutyl PV) 0.5 parts The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. The solution was then cooled to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and vacuum dried at 40°C for 24 hours to obtain polymer A1. The weight average molecular weight of polymer A1 was 68400, the melting peak temperature (melting point) was 62°C, and the acid value was 0.0 mgKOH / g. The polymer A1 was analyzed by NMR and found to contain 28.9 mol % of monomer units derived from behenyl acrylate, 53.8 mol % of monomer units derived from methacrylonitrile, and 17.3 mol % of monomer units derived from styrene. The SP values of the monomer units were also calculated.
[0083] <Production Examples of Polymers A2 to A17> Polymers A2 to A17 were obtained by carrying out the reaction in the same manner as in the production example of polymer A1, except that the monomers and the parts by mass thereof were changed as shown in Table 2. Table 2 shows their physical properties.
[0084] [Table 2] In the table, "1st" refers to the first monomer unit (polymerizable monomer), and "2nd" refers to the second "3rd" indicates a third monomer unit (polymerizable monomer). The acid value is in mgKOH / g, the melting point is in °C, and the molecular weight is the weight average molecular weight.
[0085] The abbreviations in Table 2 are as follows: BEA: Behenyl acrylate SA: Stearyl acrylate MYA: Myricyl acrylate OA: Octacosyl acrylate HA: Hexadecyl acrylate MN: Methacrylonitrile AN: Acrylonitrile HPMA: 2-hydroxypropyl methacrylate AM: Acrylamide VA: Vinyl acetate MA: Methyl acrylate St: styrene MM: Methyl methacrylate
[0086] <Toner 1 Manufacturing Example> Binder resin P1 100.0 parts Polymer A1 5.0 parts Fischer-Tropsch wax (maximum endothermic peak temperature 90°C) 6.0 parts CI Pigment Blue 15:3 9.0 parts The raw materials shown in the recipe were mixed in a Henschel mixer (FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 20 s. -1 After mixing for 5 minutes, the mixture was kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation) set at a temperature of 130° C. and a barrel rotation speed of 200 rpm. The kneaded product obtained was cooled and coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product obtained was finely pulverized using a mechanical pulverizer (T-250, manufactured by Turbo Kogyo Co., Ltd.). Classification was further performed using a rotary classifier (200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The weight average particle size (D4) of the obtained toner particles 1 was 6.5 μm. To the obtained toner particles, 1:100.0 parts, hydrophobic silica (BET: 200m 2 2.0 parts of 100g of 100% ethanol was mixed in a Henschel mixer (FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 100° C. for 5 minutes and passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain Toner 1.
[0087] <Production Examples of Toners 2 to 31> Toners 2 to 31 were obtained in the same manner as in the production example of toner 1, except that the types and amounts of binder resin and polymer A were changed to those shown in Table 3. The weight average particle size (D4) of the obtained toner particles 2 to 31 was all 6.5 μm.
[0088] [Table 3]
[0089] <Manufacturing example of magnetic core particles> (Step 1: Weighing and mixing step) Fe 2 O 3 62.7 copies ·MnCO 3 29.5 copies Mg(OH) 2 6.8 parts SrCO 3 1.0 copies The ferrite raw materials were weighed so as to obtain the above-mentioned composition ratio, and then crushed and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch. (Step 2: Pre-firing step) The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then passed through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the resulting calcined ferrite was as follows: (MnO) a (MgO) b (SrO) c (Fe 2 O 3 ) d In the above formula, a = 0.257, b = 0.117, c = 0.007, d = 0.393
[0090] (Step 3: Crushing step) The calcined ferrite was crushed to about 0.3 mm using a crusher, and then 100 parts of the calcined ferrite were mixed with 30 parts of water and crushed in a wet ball mill for 1 hour using zirconia beads with a diameter of 1 / 8 inch. The obtained slurry was then passed through an aluminum navi with a diameter of 1 / 16 inch. The mixture was pulverized for 4 hours in a wet ball mill using a calcined ferrite slurry (finely pulverized calcined ferrite). (Process 4: Granulation process) To the ferrite slurry, 1.0 part of ammonium polycarboxylate as a dispersant and 2.0 parts of polyvinyl alcohol as a binder were added per 100 parts of calcined ferrite. The mixture was then granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki Co., Ltd.). The resulting particles were adjusted in particle size, and then heated at 650°C for 2 hours in a rotary kiln to remove the organic components of the dispersant and binder.
[0091] (Step 5: Firing step) In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less. (Step 6: Sorting step) After the aggregated particles were crushed, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles 1 having a volume distribution-based median diameter of 37.0 μm.
[0092] [Preparation of coating resin] Cyclohexyl methacrylate 26.8% by mass Methyl methacrylate 0.2% by mass Methyl methacrylate macromonomer 8.4% by mass (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) Toluene 31.3% by mass Methyl ethyl ketone 31.3% by mass Azobisisobutyronitrile 2.0% by mass Of the above materials, cyclohexyl methacrylate, methyl methacrylate, methyl methacrylate macromonomer, toluene, and methyl ethyl ketone were placed in a four-neck separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer. Nitrogen gas was introduced into the separable flask to replace the inside of the system with nitrogen gas. After that, the temperature was raised to 80°C, and azobisisobutyronitrile was added and polymerized by refluxing for 5 hours. Hexane was poured into the obtained reaction product to precipitate a copolymer, and the precipitate was filtered and then vacuum dried to obtain coating resin 1. 30 parts of the obtained coating resin 1 was dissolved in 40 parts of toluene and 30 parts of methyl ethyl ketone to obtain polymer solution 1 (solid content 30 mass %).
[0093] [Preparation of coating resin solution] ·Polymer solution 1 (resin solid content concentration 30%) 33.3% by mass Toluene 66.4% by mass Carbon black 0.3% by mass (Primary particle size 25 nm, nitrogen adsorption specific surface area 94 m 2 / g, DBP oil absorption 75mL / 100g) The above materials were dispersed for 1 hour using zirconia beads having a diameter of 0.5 mm in a paint shaker. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution 1.
[0094] [Magnetic carrier manufacturing example] (Resin coating process) Coating resin solution 1 was added to a vacuum degassing kneader maintained at room temperature so that the ratio of resin components was 2.5 parts per 1:100 parts of magnetic core particles. After addition, the rotation speed was 30 rpm. After the solvent had evaporated to a certain extent (80% by mass), the temperature was raised to 80° C. while mixing under reduced pressure, and the toluene was distilled off over 2 hours, followed by cooling. The obtained magnetic carrier was subjected to magnetic separation to separate out low magnetic particles, which were passed through a sieve with openings of 70 μm and then classified with an air classifier to obtain Magnetic Carrier 1 having a volume distribution-based median diameter of 38.2 μm.
[0095] <Production Examples of Two-Component Developers 1 to 31> Each of the toners 1 to 31 and the magnetic carrier 1 (number average particle size 35 μm) were mixed in a V-type mixer (V-10 type: Tokuju Seisakusho Co., Ltd.) for 0.5 s so that the toner concentration was 9% by mass. -1 The mixture was mixed for 5 minutes to obtain two-component developers 1 to 31.
[0096] <Toner Evaluation> The image forming apparatus used for evaluation was a modified Canon full-color copier imagePRESS C800. This image forming apparatus has a photoconductor that forms an electrostatic latent image as an image carrier, and has a developing process in which the electrostatic latent image on the photoconductor is developed into a toner image by a two-component developer. It also has a transfer process in which the developed toner image is transferred to an intermediate transfer body, and then the toner image on the intermediate transfer body is transferred to paper, and a fixing process in which the toner image on the paper is fixed by heat. The image forming apparatus was modified so that the fixing temperature and process speed could be changed.
[0097] [Charge stability evaluation] The charge amount of the toner on the electrostatic latent image carrier was measured by a Faraday Cage to evaluate the charging stability. A Faraday cage is a coaxial double cylinder, with the inner and outer cylinders insulated. If a charged object with a charge Q is placed inside the inner cylinder, electrostatic induction will create the same effect as if a metal cylinder with a charge Q were present. The amount of induced charge was measured with an electrometer (Kessley 6517A, Kessley), and the charge Q (mC) divided by the toner mass M (kg) in the inner cylinder (Q / M) was determined as the charge per unit mass. Paper: CS-680 (68.0g / m 2 )(Canon Marketing Japan Inc.) Evaluation image: A 2cm x 5cm image placed in the center of the A4 paper. Toner load on paper: 0.35mg / cm 2 (The DC voltage of the developer carrier V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Test environment: High temperature and humidity environment (temperature 30℃ / humidity 80% RH (hereinafter H / H)) Process speed: 377mm / s The two-component developer 1 was charged into the developing device of the cyan station of the image forming apparatus, and an evaluation was performed. For stabilization of the evaluation machine, 10 sheets of A4 paper were output using a band chart with an image ratio of 0.1%. After that, the above evaluation image was formed on the electrostatic latent image carrier, and before it was transferred to the intermediate transfer body, the rotation of the electrostatic latent image carrier was stopped and the toner on the electrostatic latent image carrier was suctioned and collected using a metal cylindrical tube and a cylindrical filter. At that time, the charge amount Q stored in the capacitor through the metal cylindrical tube and the mass M of the collected toner were measured, and the charge amount per unit mass Q / M (mC / kg) was calculated from the result, and the initial Q / M (mC / kg) on the electrostatic latent image carrier was measured. Next, the developer was left in the evaluation machine in a H / H environment for 2 weeks, and then the evaluation machine was started and the Q / M (mC / kg) on the electrostatic latent image carrier after the test was measured in the same manner as before the test. The Q / M retention rate on the electrostatic latent image carrier after the test was calculated using the following formula. The Q / M retention rate on the electrostatic latent image carrier after the test was evaluated according to the following evaluation criteria. Maintenance rate of Q / M on electrostatic latent image carrier after durability test = {Q / M on electrostatic latent image carrier after durability / Q / M on electrostatic latent image carrier at the beginning} x 100 (Evaluation Criteria) A: Q / M maintenance rate is 95% or higher B: Q / M maintenance rate is 90% or more but less than 95% C: Q / M maintenance rate is between 85% and 90% D: Q / M maintenance rate is 80% or more but less than 85% E:Q / M maintenance rate is between 75% and 80% F:Q / M maintenance rate is less than 75%
[0098] [Image scratch resistance evaluation] Paper: SPLENDLUX135 (135.0 g / m 2 ) (Feridoni) Evaluation image: A 2cm x 15cm image placed in the center of the A4 paper. Toner amount on paper: 0.90mg / cm 2 (The DC voltage of the developer carrier V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Test environment: Normal temperature and humidity (temperature 23°C, humidity 50% RH (hereinafter N / N)) Process speed: 248mm / s The two-component developer 1 was charged into the developing devices of the cyan station and magenta station of the image forming apparatus, and an evaluation was performed. The evaluation image was printed at a fixing temperature of 170°C. The recording paper on which the above evaluation image was formed was subjected to a surface test using a HEIDON surface tester manufactured by Shinto Scientific Co., Ltd. Using a TYPE14FW, a 200g weight was placed on the image and scratched with a Φ0.75mm needle at a speed of 60mm / min and a length of 30mm to evaluate image scratch resistance. The area ratio where the toner peeled off was binarized by image processing. (Evaluation Criteria) A: The image is free of scratches. B: Image scratches occurred. The area ratio of toner peeled off is less than 1.0%. C: Image scratches occurred. The area ratio of toner peeled off was 1.0% or more and less than 2.0%. D: Image scratches occurred. The area ratio of toner peeled off was 2.0% or more and less than 4.0%. E: Image scratches occurred. The area ratio of toner peeled off was 4.0% or more and less than 6.0%. F: Image scratches. Toner peeled off area ratio is 6.0% or more.
[0099] Two-component developers 2 to 31 were also evaluated in the same manner as two-component developer 1. The results are shown in Table 4.
[0100] [Table 4]
Claims
1. A toner having toner particles containing a binder resin and a polymer A, The binder resin contains a polyester resin having a structure represented by the following formula (B): In formula (B), R X each independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, , and -R 20 N.H. 2 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10 to 80; The polymer A has a first monomer unit having a structure represented by the following formula (I) and a second monomer unit different from the first monomer unit, In formula (I), R Z1 represents a hydrogen atom or a methyl group, R represents an alkyl group having 18 to 36 carbon atoms, a content ratio of the first monomer unit in the polymer A is 5.0 mol % to 60.0 mol % based on the total number of moles of all monomer units in the polymer A, the content ratio of the second monomer unit in the polymer A is 20.0 mol % to 95.0 mol % based on the total number of moles of all monomer units in the polymer A, The SP value of the first monomer unit is SP1 (J / cm 3 ) 0.5 The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 In the structure represented by formula (B), -(Si(R X ) 2 O) n -Si(R X ) 2 The SP value of the silicone portion represented by - is SP3 (J / cm 3 ) 0.5 The toner is characterized by satisfying the following formulas (1) to (3): SP1≦18.4 ... (1) 21.0≦SP2 ... (2) SP1-SP3<SP2-SP1...(3)
2. 2. The toner according to claim 1, wherein the second monomer unit is at least one selected from the group consisting of the following formulae (II) and (III): In formula (II), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 1 is -C≡N, -C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy groups, -COOR 11 (R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; -NHCOOR 12 (R 12 represents an alkyl group having 1 to 4 carbon atoms), -NH-C(=O)-N(R 13 ) 2 (Two R 13 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. -COO(CH 2 ) 2 NHCOR 14 (R 14 represents an alkyl group having 1 to 4 carbon atoms; -COO(CH 2 ) 2 -NH-C(=O)-N(R 15 ) 2 (Two R 15 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. It is. 2 represents a hydrogen atom or a methyl group. In formula (III), R 3 represents an alkyl group having 1 to 4 carbon atoms; R 4 represents a hydrogen atom or a methyl group.
3. 3. The toner according to claim 1, wherein the content of the polymer A is from 1.0 part by mass to 10.0 parts by mass with respect to 100 parts by mass of the binder resin.
4. In the formula (I), R Z1 4. The toner according to claim 1, wherein R is a hydrogen atom and R is an alkyl group having 22 carbon atoms.
5. 5. The toner according to claim 1, wherein the content of the silicone moiety in the polyester resin having the structure represented by formula (B) is 0.5% by mass or more and 5.0% by mass or less.
6. In the formula (B), R X The toner according to any one of claims 1 to 5, wherein each of the is a methyl group.
7. The toner according to any one of claims 1 to 6, wherein the SP2 satisfies the following formula (2)': 25.0≦SP2≦30.0 ... (2)'
8. 8. The toner according to claim 1, wherein the content of the polyester resin having the structure represented by formula (B) in the binder resin is 50% by mass or more.
Citation Information
Patent Citations
Composite polyester resin
JP2002012657A
Resin for toner, toner, developer, and image forming apparatus
JP2012242448A
toner
JP2019219647A
Toner binder
WO2019225207A1
